Incidence of extended-spectrum beta-lactamase-producing Klebsiella pneumoniae in patients with urinary tract infection - Ghafourian, Sobhan (2012)
CONTEXT AND OBJECTIVES: Resistant bacteria are emerging worldwide as a threat to favorable outcomes from treating common infections in community and hospital settings. The present investigation was carried out to study the incidence of extended-spectrum beta-lactamase (ESBL)-producing Klebsiella pneumoniae in patients with urinary tract infection in different seasons of the year, in order to determine the prevalence of the genes blaTEM, blaSHV and blaCTX-M, which are responsible for ESBL production among ESBL-producing K. pneumoniae, in three cities in Iran, and to investigate the antimicrobial susceptibility pattern of K. pneumoniae in different seasons. DESIGN AND SETTING: Retrospective study carried out among patients with urinary tract infections in five hospitals in Iran. METHOD: Two hundred and eighty-eight clinical isolates of K. pneumoniae were collected between March 2007 and April 2008 from five hospitals in three cities in Iran. ESBLs were identified by phenotypic and genotypic methods. ESBL-producing Klebsiella pneumoniae were evaluated against non-beta-lactam antibiotics. Genes coding for ESBLs (blaSHV, TEM and CTX-M) were screened. RESULTS: Among the 288 clinical isolates of K. pneumoniae, 37.7%, 46.7% and 15.6% were obtained from hospitals in Ilam, Tehran and Tabriz, respectively, of which 39.4%, 50.7% and 45.8% were ESBL-producing K. pneumoniae in Ilam, Milad and Emam Reza hospitals, respectively. CONCLUSION: According to the results from this study, resistance to third-generation cephalosporins is higher during the cold months than during the warm months.